PENGARUH THIN CAPITALIZATION TERHADAP PENGHINDARAN PAJAK - NASAIHATUL AFIFAH, SITI; PRASTIWI, DEWI (Jurnal Akuntansi AKUNESA, 2019)
This study aim to provide empirical evidence to examine the determining thin capitalization toward tax avoidance in multinational and domestic companies are listed on Indonesia stock exchange during period 2014 until 2017. This research employed purposive sampling method based on the certain criteria, they were 134 samples. Simple regression analysis was used as an analytical technique in this study. The result showed that thin capitalization effect toward tax avoidance on multinational companies and domestic companies. Based on additional analysis used independent sample t test, these results indicate that there were thin capitalization between multinational companies and domestic companies. Multinational companies to be more leveraged than domestic companies.